Зміст забов'язальних іпотечних правовідносин - Чанишева, Аліна Рашидівна; Чанышева, Алина Рашидовна; Chanysheva, A. (My University, 2012)
In the article allocation of obligation and proprietary mortgage civil legal relations is grounded. The content of obligation mortgage civil legal relations as of a part of legal construction of mortgage is deﬁ ned.
Чанишева А. Р. Зміст забов'язальних іпотечних правовідносин / А. Р. Чанишева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 261- 268.
Keywords: забов'язання іпотечних правовідносин; іпотечні правовідносини; зобов’язальні правовідносини; відносні іпотечні правовідносини; относительные ипотечные правоотношения; обязательственные правоотношения; ипотечные правоотношения; обязательства ипотечных правоотношений; relative legal mortgage; relationship of obligation; legal mortgage; legal obligations of mortgage